A Blended Learning Model for Learning Achievement Enhancement of Thai Undergraduate Students - Wirachat Banyen; Chantana Viriyavejakul; Thanin Ratanaolarn (My University, 2016)
Research was undertaken to develop a blended learning model which contained three objectives. They were to 1) study student and teacher input for a blended learning model using a Thai university undergraduate course in information, innovation, and technology in education for the learning management conditions and improvement methods; 2) to research how to effectively improve the blended learning model and instructional media in accordance with the 80/80 criteria and; 3) compare learning achievements and information literacy between student groups using the blended learning method and regular learning method with information literacy as the covariate. The research was divided into three phases consisting of the development of the conceptual framework, a second phase which studied the blended learning model using both e-learning and face-to-face methods with a 60/40 ratio. When applying a technology system to learning management utilizing instructional media, it was determined to be 81.53/80.11. Phase 3 found that blended learning affected learning and information literacy by at least 1 variate which had a different mean score from regular learning with a statistical significance at the 0.05 level. The findings showed that the Thai university undergraduate students were satisfied with the blended learning model which was due to the change in the learning system as well as being tasked with interesting and challenging computer based lessons outside class. This was later enforced through teacher delivered lesson summaries during formal class time. Students understood the content better, enjoyed the self-directed learning and doing things independently.
Keywords: Blended Learning; Online and Blended Learning